KECERDASAN BUATAN DAN PERAN PUSTAKAWAN DALAM REVOLUSI PENELITIAN - Prayitno, Dio Eka; Fathurohman, Zaki; Putri, Soraya Hariyani; Isniwati, Arif (Perpustakaan Nasional RI, 2024)
Artificial intelligence and the role of librarians are currently a unique combination in the world of libraries, especially digital libraries. On the one hand, librarians have occupied the main position in libraries as individuals who search, manage, and distribute knowledge. Then, there is artificial intelligence that complements and covers things that librarians have not been able to fulfill. One of them is helping to explore research topics that have not been touched by researchers or the academic and general public. This technology certainly cannot run alone unless there are individuals who direct and drive so that the information obtained is in accordance with the needs of the library users, is useful appropriately, and efficient in its use. Simple but still trying to answer the question of how librarians use artificial intelligence to identify topics that have not been maximally explored. This paper was written using bibliometric methods and literature studies. The bibliometric method and literature studies begin with determining the research topic and collecting data from relevant sources, followed by analysis and interpretation of the results to identify trends and deviations in the research. After that, the literature obtained is evaluated and recommended based on the theme to compile a comprehensive critical analysis. Finally, the results of the analysis are compiled in a report that includes a summary, implications, and recommendations for further research. Based on this, the role of librarians can be maximized by utilizing AI to identify unexplored research, especially in the field of library and information science and it is necessary to see several things that artificial intelligence can do in the world of research. Some of them are 1. Artificial intelligence can increase the accessibility and efficiency of research; 2. Artificial intelligence can evolve research; 3. Librarians can utilize artificial intelligence to optimize the development of a curriculum in a field of science; 4. Librarians can use artificial intelligence to provide remote services; 5. Librarians can help researchers and academics to create or connect researcher networks based on publications and research activities. The conclusion of this paper is that librarians who can utilize artificial intelligence will be able to identify and help explore various studies. This will create a revolution in research in a field.